Hepatitis B Virus RNA as Early Predictor for Response to Pegylated Interferon Alpha in HBeAg-Negative Chronic Hepatitis B. (8th January 2020) - Farag, Mina S; van Campenhout, Margo J H; Pfefferkorn, Maria; Fischer, Janett; Deichsel, Danilo; Boonstra, André; van Vuuren, Anneke J; Ferenci, Peter; Feld, Jordan J; Berg, Thomas; Hansen, Bettina E; van Bömmel, Florian; et al.
Abstract: Background: Hepatitis B virus RNA (HBV-RNA) is a novel serum biomarker that correlates with transcription of intrahepatic covalently closed circular (cccDNA), which is an important target for pegylated interferon (PEG-IFN) and novel therapies for functional cure. We studied HBV-RNA kinetics following PEG-IFN treatment and its potential role as a predictor to response in HBeAg-negative chronic hepatitis B (CHB) patients. Methods: HBV-RNA levels were measured in 133 HBeAg-negative CHB patients treated in an international randomized controlled trial (PARC study). Patients received PEG-IFN α-2a for 48 weeks. HBV-RNA was measured from baseline through week 144. Response was defined as HBV-DNA <2000 IU/mL and ALT normalization at week 72. Kinetics of HBV-RNA were compared with HBV-DNA, HBsAg, and HBcrAg. Results: Mean HBV-RNA at baseline was 4.4 (standard deviation [SD] 1.2) log10 c/mL. At week 12, HBV-RNA declined by −1.6 (1.1) log10 c/mL. HBV-RNA showed a greater decline in responders compared to nonresponders early at week 12 (−2.0 [1.2] vs −1.5 [1.1] log10 c/mL, P = .04). HBV-RNA level above 1700 c/mL (3.2 log10 c/mL) had a negative predictive value of 91% at week 12 and 93% at week 24 ( P = .01) for response. Overall, HBV-RNA showed a stronger correlation with HBV-DNA and HBcrAg (.82 and .80, P < .001) and a weak correlation with HBsAg (.25). At week 12, HBV-RNA was significantly lower among patients with lower HBsAg (<100 IU/mL) or HBsAg loss at week 144. Conclusions: During PEG-IFN treatment for HBeAg-negative CHB, HBV-RNA showed a fast and significant decline that correlates with treatment response and HBsAg loss at long-term follow-up. Clinical Trials Registration: NCT00114361 Abstract : Hepatitis B Virus-Pegylated Interferon (HBV-RNA) declined early during PEG-IFN treatment among patients achieved response and HBsAg loss. Serum HBV-RNA is a potential negative predictor of clinical response at week 12 of therapy. HBV-RNA may increase response rates to PEG-IFN treatment in HBeAg-negative patients.